An in situ investigation of the solute suppressed nucleation zone in an Al-15 wt% Cu alloy inoculated by Al-Ti-B. (1st July 2019) - Jia, Yiwang; Huang, Haijun; Fu, Yanan; Zhu, Guoliang; Shu, Da; Sun, Baode; StJohn, D.H.
Abstract: The solute concentration profile ahead of the solid-liquid (S-L) interface and the size of the solute suppressed nucleation zone (SSNZ) were studied in situ by synchrotron X-ray radiography during the solidification of Al-15 wt% Cu alloy inoculated by Al-Ti-B. The measured solute distribution ahead of the S-L interface and the size of SSNZ were in the range between the predictions from the steady-state and transient growth models. Both the size of SSNZ and the spacing between the activated nucleants decreased with increasing cooling rate, contributing equally to the decrease of final grain size. Graphical abstract: The measurement of solute suppressed nucleation zone.Unlabelled Image